Corporate responsibility and the plurality of market aims. (7th May 2019) - Smith, Jeffery
Abstract: A number of recent authors, most notably Joseph Heath, have persausively defended a market‐centered account of corporate responsibility that grounds standards of business conduct upon the normative presuppositions of the market. They have us focus on two important items: first, the value of welfare, or Pareto efficient outcomes, which underwrites the legitimacy of market arrangements; and second, the behavioral requirements needed to assure that corporations conduct business in a manner consistent with this value. This article critically examines the aspirations of this literature by embracing its basic method but questioning how well it understands the aim of the market. It puts forth a limited case for corporate responsibility anchored in other dimensions of the public good, distinct from the value of efficiency, and argues that a plausible understanding of corporate responsibility arises from the notion that market arrangements are sites of delegated social authority to provision other aspects of the common good.